Effect of various organic on growth and yield of cabbage (Brassica oleracea L.) - Chanu Nongthombam Cherri; Sanasam Justine; Maisnam Guneshori; Thakur Deepshikha (BIO Web of Conferences)
This study evaluates the effects of organic manures and biofertilizers on the growth and yield of cabbage (Brassica oleracea var. capita). A field experiment was conducted using a randomized block design to assess the impact of farmyard manure, vermicompost, poultry manure, and their combinations with biofertilizers on cabbage production. Growth parameters such as plant height, number of outer leaves, and head diameter were measured at different stages, while yield parameters were recorded at harvest. The results indicated that organic fertilizers significantly improved cabbage growth and productivity compared to the control. Treatments incorporating farmyard manure and vermicompost combined with biofertilizers exhibited superior performance in plant growth and yield. These treatments enhanced soil fertility, promoted better nutrient uptake, and supported healthy plant development. The study suggests that the use of organic amendments can reduce the dependency on chemical fertilizers, minimizing their adverse environmental effects while maintaining agricultural sustainability. Furthermore, organic fertilizers contribute to improved soil health by increasing microbial activity, enhancing water retention, and maintaining soil structure. The findings highlight the importance of integrating organic manures and biofertilizers into farming practices to achieve better crop performance while ensuring long-term soil productivity. This study reinforces the role of organic farming in sustainable agriculture, offering an eco-friendly alternative to conventional chemical-based cultivation methods. Future research can focus on optimizing organic fertilizer application rates and assessing their long-term impact on different crop varieties.